Pengaruh Bauran Pemasaran (Marketing Mix 4P) Terhadap Keputusan Pembelian Di Cafe Pare Bercerita - Muhammad Machrizan Nabil (CEMERLANG : Jurnal Manajemen dan Ekonomi Bisnis, 2024)
This research aims to determine the influence of price, place, product and promotion variables on purchasing decisions at Cafe Pare Bercerita. This type of research is quantitative research which is used to test the relationship of a variable to other variables which emphasizes the analysis on numbers processed using statistical methods. This research data was obtained through questionnaires, interviews and literature studies. The analysis techniques used are Validity Test, Reliability Test, Classical Assumption Test, Multiple Linear Regression Analysis, T Test, F Test and Coefficient of Determination Test. The results of the t test for the price variable (X1) have a partially significant effect on purchasing decisions. Place (X2) has a partially significant effect on Purchase Decisions. Product (X3) has a partially significant effect on purchasing decisions. Promotion (X4) has a partially significant effect on purchasing decisions. The results of the F test can be concluded that price, place, product and promotion have a simultaneous and significant effect on purchasing decisions at Cafe Pare Bercerita.